1984
DOI: 10.1152/ajpregu.1984.246.5.r811
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of microinjections of angiotensin II in the brain stem of rats

Abstract: The blood pressure and heart rate responses to microinjection of angiotensin II (ANG II) into the brain stem of urethan-anesthetized rats were studied. Microinjection of ANG II into the area postrema (AP) resulted in significant elevation of blood pressure and significant reduction of heart rate. Microinjection into the region of the nucleus tractus solitarius (NTS) yielded a significant dose-dependent elevation in blood pressure and consistent increases in heart rate. The response to microinjection of ANG II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
1
32
1
1
Order By: Relevance
“…Norepinephrine, acetylcholine, epinephrine, Lglutamate, dopamjne, and other agents are known to reduce blood pressure and heart rate when injected into the NTS. In contrast, certain agents, such as angiotensin II, 26 vasopressin, 27 and yohimbine, 28 have been shown to raise blood pressure and heart rate when injected into this site.…”
Section: Discussionmentioning
confidence: 94%
“…Norepinephrine, acetylcholine, epinephrine, Lglutamate, dopamjne, and other agents are known to reduce blood pressure and heart rate when injected into the NTS. In contrast, certain agents, such as angiotensin II, 26 vasopressin, 27 and yohimbine, 28 have been shown to raise blood pressure and heart rate when injected into this site.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is not surprising that this nucleus has been suggested as a main region for Ang influencing baroreceptor afferent information (8,54) as well as the integration of chemoreceptor afferents (54). In anesthetized rats, microinjection of Ang into the NTS produces pressor responses at nmol doses (55) and depressor responses at pmol doses (56), and attenuates the baroreceptor reflex (57,58) through AT 1 receptors. Our own studies in anesthetized rabbits are consistent with these findings since we observed mainly depressor responses to 1 pmol Ang II injected into the dorsomedial region.…”
Section: Ang Actions Within the Nucleus Tractus Solitariusmentioning
confidence: 99%
“…81 Microinjection of Ang II into the nucleus of the solitary tract produces depressor (low-dose) and pressor responses. 82,83 The pressor response involves activation of sympathetic efferent pathways. The rostral ventrolateral medulla contains a population of sympathetic premotor neurons whose tonic activity is essential for the maintenance of sympathetic vasomotor tone and normal resting BP.…”
Section: Sympathetic Nerve Activitymentioning
confidence: 99%